Pengaruh Tanggung Jawab Sosial dan Modal Intelektual terhadap Kinerja Keuangan Perusahaan (Studi pada BUMN yang Terdaftar di Bursa Efek Indonesia) - Rahmatiah, Rahmatiah; Hidayah, Noor Riefma (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Tadulako, 2018)
This research aims to know and analyze the effect of social responsibility and intellectual capital both simultaneously and partially to company’s financial performance at state-owned enterprise (BUMN) listed on the Indonesia Stock Exchange. The type of research is quantitative and with the using secondary data. The total sample is nine companies which the research period is 2011-2015. Results show that simultaneously corporate social responsibility and intellectual capital influence the finance performance. Corporate social responsibility do not have effect while intellectual capital influence the financial performance partially.